Resort Complex of the Russian Federation: Modern Aspect of Development - Anischenko, Elena A.; Stas, Narin T.; ChurÃ¡Åˆov, Alim B.; Tenova, Zalina Y.; Chakarova, Lina H. (International Journal of Economics and Financial Issues, 2016)
Contemporary Russian resort complex (RC) is a unique phenomenon, specific for a number of post-Soviet countries. Its originality is due to the origin of the Soviet sanatorium system prevailing social orientation, orientation to therapeutic measures. Despite the fact that a number of experts proposes to consider the activities of the sanatorium organizations in the framework of an independent economic activity, more informed opinion that in this case there is the operation of an interbranch complex organizations engaged in various activities, such as "spa establishments (sanatoriums, sanatorium, balneogryazelechebnitsy, boarding houses with treatment, children's camps of sanatorium type), which are medical institutions; recreation (holiday resorts, holiday homes, camp sites, camps), "hotels and other accommodations collective accommodation, which are considered public utilities," located in the resorts catering; "tourist and excursion companies, related to the tourism sector," the organization Various recreational services and entertainment, culture and sports. Therefore resort complex can be defined as cross-sectoral integration of different organizations specializing in the provision of health, wellness and recreational services, which are located in the resort areas and are used in the activity of natural and recreational resources, while maintaining their specific expertise. Keywords: resort complex, tourism, resort infrastructure, market JEL Classifications: L83, M38